IMPLEMENTING A NEW EDUCATIONAL MODEL OF THE BACHELOR COURSE: EXPERIENCE OF THE PLEKHANOV RUSSIAN UNIVERSITY OF ECONOMICS - Evgeniya V. Shubenkova; Aleksandr L. Bobkov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article deals with acute issues of the present day Russian higher education, which are connected with the necessity to raise its quality and its competitiveness on the global market of education. The authors put forward new approaches to the development of educational programs for bachelors in conditions of cost optimization at the Russian Plekhanov University of Economics. A standard structure for the educational program for bachelors was presented and key features of its implementation were described, such as the use of module principle, basic subjects equal in labour-intensity, including adaptive subjects for learners with limited health possibilities and disability, broad introduction of electronic and project studying.